Gymnaconitum, a new genus of Ranunculaceae endemic to the Qinghai–Tibetan Plateau. Issue 4 (27th December 2018) - Wang, Wei; Liu, Yang; Yu, Sheng-Xiang; Gao, Tian-Gang; Chen, Zhi-Duan
Abstract: The monophyly of traditional Aconitum remains unresolved, owing to the controversial systematic position and taxonomic treatment of the monotypic, Qinghai–Tibetan Plateau endemic A. subg. Gymnaconitum . In this study, we analyzed two datasets using maximum likelihood and Bayesian inference methods: (1) two markers (ITS, trnL–F ) of 285 Delphinieae species, and (2) six markers (ITS, trnL–F, trnH–psbA, trnK–matK, trnS–trnG, rbcL ) of 32 Delphinieae species. All our analyses show that traditional Aconitum is not monophyletic and that subgenus Gymnaconitum and a broadly defined Delphinium form a clade. The SOWH tests also reject the inclusion of subgenus Gymnaconitum in traditional Aconitum . Subgenus Gymnaconitum markedly differs from other species of Aconitum and other genera of tribe Delphinieae in many non–molecular characters. By integrating lines of evidence from molecular phylogeny, divergence times, morphology, and karyology, we raise the monotypic A. subg. Gymnaconitum to generic status.